Metabolic Labeling of Peptidoglycan with NIR‐II Dye Enables In Vivo Imaging of Gut Microbiota. Issue 7 (9th January 2020) - Wang, Wei; Yang, Qinglai; Du, Yahui; Zhou, Xiaobo; Du, Xiaochen; Wu, Qiuyue; Lin, Liyuan; Song, Yanling; Li, Fuyou; Yang, Chaoyong; Tan, Weihong
Abstract: Deepening our understanding of mammalian gut microbiota has been greatly hampered by the lack of a facile, real‐time, and in vivo bacterial imaging method. To address this unmet need in microbial visualization, we herein report the development of a second near‐infrared (NIR‐II)‐based method for in vivo imaging of gut bacteria. Using d ‐propargylglycine in gavage and then click reaction with an azide‐containing NIR‐II dye, gut microbiota of a donor mouse was strongly labeled with NIR‐II fluorescence on their peptidoglycan. The bacteria could be readily visualized in recipient mouse gut with high spatial resolution and deep tissue penetration under NIR irradiation. The NIR‐II‐based metabolic labeling strategy reported herein, provides, to the best of our knowledge, the first protocol for facile in vivo visualization of gut microbiota within deep tissues, and offers an instrumental tool for deciphering the complex biology of these gut "dark matters". Abstract : A real‐time in vivo imaging method to fulfill the unmet need for gut microbiota visualization was developed by integrating the strategy of d ‐amino‐acid‐based metabolic labeling and NIR‐II fluorescence imaging. The versatility of this technique was demonstrated in imaging different bacterial species, and in the study of gastrointestinal motility‐induced gut microbiota biogeography changes.